2020
DOI: 10.3390/en13040850
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of an Adaptive Neuro-Fuzzy Inference System to Predict the Relationship among Energy Intensity, Globalization, and Financial Development in Major ASEAN Economies

Abstract: The enhancement of the financial sector significantly drives a nation’s economy and thereby increase energy intensity. Considering this situation, the current study aims to examine the link between globalization and financial advancements with the energy intensity of the top 5 ASEAN (Association of Southeast Asian Nations) economies. The development structure of the ASEAN region is considered significant for having stable growth. The authors used the annual data from 1990 to 2018 for five of the largest ASEAN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…As global economics grows rapidly, one of the negative aspects is the over consumption of energy that leads to global warming and damages the ecological environment [1,2]. China is also facing an energy over-consumption problem [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As global economics grows rapidly, one of the negative aspects is the over consumption of energy that leads to global warming and damages the ecological environment [1,2]. China is also facing an energy over-consumption problem [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[8] revealed that financial development lowers energy intensity using the case of Ghana. [9] confirmed financial development are positively correlated and have a significant impact on the energy intensity level in the top ASEAN countries. However, as a subset of the more general literatures on energy intensity, very few studies have focused on finding the impact of urbanization and financial development on electricity intensity.…”
Section: Introductionmentioning
confidence: 79%
“…The analysis of the literature in this paper indicates that so far the authors have focused on improving the efficiency of electricity use and reliability [2,5,12,13,23] and on technical aspects of schemes and possible innovative solutions [25][26][27][28][29] that automate processes which improve stability in the power system.…”
Section: Discussionmentioning
confidence: 99%
“…This paper has come out with the solution methods to analyze the way of enhancing the economy and dependability of China's distributing system planning by the optimal utilization of distributed generation and resources of DSR. Due to the great technological advancements of most power network transmission systems, the majority of available DSR literature concerns the development of smart grids [20][21][22], including an adaptive neuro-fuzzy inference system to predict the relationship among energy intensity and globalization [23].…”
Section: Literature Reviewmentioning
confidence: 99%